Abelian theorems for Whittaker transforms - Richard D. Carmichael; R. S. Pathak (International Journal of Mathematics and Mathematical Sciences)
Initial and final value Abelian theorems for the Whittaker transform of functions and of distributions are obtained. The Abelian theorems are obtained as the complex variable of the transform approaches 0 or ∞ in absolute value inside a wedge region in the right half plane.